An investigation into the factors affecting player development within each phase of the academy pathway in english football academies. (4th July 2021) - Cooper, Adam
ABSTRACT: The purpose of this research project is to build upon the limited base of academic research into the development of players through the academy pathway in English Football Academies. The unique focus of this study is to investigate the limited academic area of player development specific to each phase of the academy pathway; Foundation Phase, Youth Development Phase and Professional Development Phase. The research was conducted utilizing a questionnaire obtaining quantitative and supplementary qualitative data, designed to target aspects unique to academy environments highlighted by prior academic literature. The results present new evidence that academy football can force unnecessary stress upon players within the foundation, youth development and professional development phases, both internally through pressure to succeed and externally from parents and support networks. The research also confirms that coaching is the strongest influence upon player development, however raises new questions regarding its effectiveness across all phases within academy football.